Review of National and International Accreditation of Pharmacy Programs in the Gulf Cooperation Council Countries - Alkhateeb, Fadi M. (Am J Pharm Educ, 2018)
Objective. To compare the different philosophies, emphases and processes of national and international accreditation paths available to pharmacy programs in Gulf Cooperation Council (GCC) countries. To identify engagement of GCC pharmacy programs with International Pharmacy Accreditation or Certification (IPAC) and the outcome advantages of IPAC compared to other national accreditation standards. Findings. National quality standards across the GCC countries are similarly structured but in different stages of development. Pharmacy specific standards are absent. Of the 44 institutions identified offering pharmacy degrees, only three out of 28 of those in the Kingdom of Saudi Arabia (KSA) and all but two out of 15 elsewhere in the GCC, have national program-level accreditation. Nine of the institutions have IPAC via either the Accreditation Council for Pharmacy Education-International Services Program (ACPE-ISP), the Canadian Council for Accreditation of Pharmacy Programs (CCAPP) or the German Accreditation Agency in Health and Social Sciences (AHPGS). None of the institutions have sought accreditation from the Australian Pharmacy Council (APC). IPAC may serve as a tool to provide specific recognition of the quality of pharmacy programs and to enhance the quality of pharmacy education in the region. Summary. In the absence of national bodies to accredit pharmacy initial training degrees, IPAC has become increasingly popular in the GCC countries. There are distinct regional differences in uptake and choice of IPAC. IPAC may serve as a tool to provide specific recognition of the quality of pharmacy programs and to enhance the quality of pharmacy education in the region in the absence of an unmet for pharmacy-specific national accreditation.